Grain boundary diffusion of Si in polycrystalline copper film. (September 2022) - Bodnár, Eszter; Takáts, Viktor; Fodor, Tamás; Hakl, József; Kaganovskii, Yuri; Yang, Guang; Yao, Xiaogang; Vad, Kálmán
Abstract: Grain boundary (GB) diffusion of Si in polycrystalline Cu film was studied in the temperature range of 403–453 K, in the C-type kinetic regime. The amorphous Si layer (80 nm) and polycrystalline Cu layer (40 nm) were successively deposited by magnetron sputtering at room temperature onto a Si (111) wafer. Appearance of Si atoms on the copper surface due to GB diffusion through the copper layer was detected by low energy ion scattering spectroscopy with high sensitivity. The depth distribution of Si in Cu grain boundaries was revealed by secondary neutral mass spectrometry. Surface morphology of Cu films was investigated by scanning tunneling microscopy. Identification of Si chemical bonds on the surface layer was made by X-ray photoelectron spectroscopy. GB diffusion coefficients were estimated by the relation used for calculation of diffusant distribution from a constant source in assumption that the diffusion path equals to the film thickness at the moment of appearing Si atoms on the Cu surface. At 453 K we estimated the surface segregation factor and detected formation of Cu–O–Si atomic bonds on the Cu film surface. Highlights: Nanoscale grain boundary diffusion of silicon. Nanoscale depth profile analysis. Application of low energy ion scattering for study of nanoscale diffusion mechanisms.